APLIKASI METODE GEOSTATISTIK MULTIVARIAT UNTUK ESTIMASI ZONA BEDROCKENDAPAN NIKEL LATERIT - Arif Budiyono (PPSDM Geominerba, 2018)
The problems in the exploration of lateritic nickel deposits arise when there was an unfinished drilling which had not penetrated the bedrock zone. This may lead to a non-optimal laterite nickel deposit resource model since the lateritic nickel mining should be carried out up to the bedrock zone. The multivariate geostatistics method was used to estimate the bedrock zone in the unfinished drilling location by utilizing the high saprolite zone elevation as the secondary data and bedrock zone elevation from the finished drilling as the primary data. Compared to the ordinary kriging, the ordinary cokriging technique approaches on multivariate geostatistics methods were proven to be able to improve the estimation results in which the statistical value of the estimated variance becomes smaller.